Lexical Devices in Children's Poetry - Ashurova, Z. Sh. (International Journal on Orange Technologies, 2023)
The article deals with the work of representatives of modern children's poetry Algor Damin and Dilshod Rajab, analyzes examples of their poetic works. Considerations are made regarding the study of lexical means, divided into such parts as synonyms, antonyms, homonyms, paronyms.